Hovenia dulcis Thunb. Honey Exerts Antiviral Effect Against Influenza A Virus Infection Through Mitochondrial Stress-Mediated Enhancement of Innate Immunity - Eun-Bin Kwon; Buyun Kim; Young-Eun Kim; Sung-Joon Na; Sang Mi Han; Soon Ok Woo; Hong Min Choi; Siwon Moon; Young Soo Kim; Jang-Gi Choi (Antioxidants)
To combat influenza A virus (IAV) infection, it is vital to develop effective therapeutic strategies, including immunomodulators. In this study, we examined the antiviral effects of Hovenia dulcis Thunb. honey (HDH) against IAV using RAW 264.7 cells. HDH treatment significantly reduced IAV infection and viral protein expression. Moreover, it enhanced the production of interferon (IFN)-β, activated the innate immune response through the cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) pathway, and upregulated IFN signaling through signal transducer and activator of transcription (STAT)1/2 phosphorylation and interferon-stimulated gene (ISG) expression. In addition, HDH decreased IAV-induced intracellular and mitochondrial reactive oxygen species (ROS) production by upregulating the expression of antioxidant proteins, such as Sirt3 and SOD2. The results suggest that HDH is a potential therapeutic agent inhibiting viral replication and boosting host antiviral immunity.